Analisis dan Perancangan Sistem Pendukung Keputusan Pemilihan Vendor Properti Event dengan Model Bobot Adaptif Berbasis Hybrid SWARA - MOORA pada PT Tri Reka Dinamis - Salsi Kirana Laura Ibra; Firman Pratama (CV. Multi Kreasi Media, 2026)
The selection of event property vendors at PT Tri Reka Dinamis faces challenges in achieving objective and consistent decision-making due to multiple evaluation criteria such as quality, cost, timeliness, and service. This study aims to design and develop a web-based decision support system using an adaptive weighting model based on the hybrid SWARA–MOORA method. The system is developed using the Waterfall model, which includes stages of analysis, design, implementation, testing, and maintenance. SWARA is used to determine the adaptive weight of each criterion, while MOORA is applied to rank and select the optimal vendor. The expected result is a functional web-based prototype capable of generating accurate, transparent, and data-driven recommendations to enhance the efficiency and fairness of vendor selection decisions.